Genetic Vulnerability to Experiencing Child Maltreatment - Pezzoli, Patrizia; Antfolk, Jan; Hatoum, Alexander S.; Santtila, Pekka (Frontiers in Genetics, 2019)
Although biological factors may influence the risk of experiencing negative life events, the role of genes in the vulnerability to child victimization remains poorly understood. In a large population-based Finnish sample (N = 13024), we retrospectively measured multiple experiences of child victimization and, in a subsample of twins (n = 9562), we estimated the extent to which genetic and environmental factors influenced these experiences. In particular, we investigated whether genetic and environmental influences varied depending on the type of child victimization, the genetic relatedness with the perpetrator, and the sex of the victim. Our quantitative genetic analyses supported the presence of both genetic and environmental influences on the occurrence and co-occurrence of child abuse and neglect. We also identified one common etiological pathway underlying multiple child victimizations, and, after accounting for this common etiology, we singled out risk factors specific to sexual abuse. Environmental factors shared and nonshared between twins raised together influenced the risk of victimization by genetically related and unrelated perpetrators respectively. Furthermore, we estimated sex differences in the etiology of emotional and sexual victimization, including larger unshared environmental influences for men and sex-limited genetic effects for women. These findings can inform child protection as they contribute to explaining why certain individuals are at increased risk of experiencing one or more types of child maltreatment.